2020
DOI: 10.1016/j.cmet.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Ketoglutarate, an Endogenous Metabolite, Extends Lifespan and Compresses Morbidity in Aging Mice

Abstract: The decline in early life mortality since the 1950s has resulted in dramatic demographic shift towards aged population. Aging manifests as a decline in health, multiple organ dysfunction and increased vulnerability to diseases, which degrades quality of life. A verity of genetic and pharmacological interventions, mostly from non-vertebrate models, have been identified that can enhance lifespan. Whether these interventions extend healthspan, the disease free and functional period of life, has only sometimes bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(155 citation statements)
references
References 54 publications
5
150
0
Order By: Relevance
“…The progression of aging is associated with critical metabolic changes. Some of these changes occur at the level of metabolites regulating the function of essential epigenetic enzymes, such as the decrease in NAD+ levels, the cofactor of sirtuins [ 41 ], and the reduction in alpha-ketoglutaric acid [ 42 ], the cofactor for all dioxygenases [ 43 ]. Although very speculative, it may be that older adults are relatively less sensitive to SARS-CoV-2-dependent epigenetic changes due to changes in their metabolic landscape.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of aging is associated with critical metabolic changes. Some of these changes occur at the level of metabolites regulating the function of essential epigenetic enzymes, such as the decrease in NAD+ levels, the cofactor of sirtuins [ 41 ], and the reduction in alpha-ketoglutaric acid [ 42 ], the cofactor for all dioxygenases [ 43 ]. Although very speculative, it may be that older adults are relatively less sensitive to SARS-CoV-2-dependent epigenetic changes due to changes in their metabolic landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Aging interventions would benefit most by applying prevention-based approaches and biomarker discovery [109]. Understanding how different physiological measures and aging clocks correspond to each other could allow targeted testing of different types of aging interventions, including the recently published life-extending molecule 2-oxoglutarate [110]. Further, João Pedro de Magalhães, University of Liverpool, UK, touched upon the topic of longevity interventions and highlighted the exponential growth of pharmacological approaches (DrugAge database), while research in genes associated with longevity have plateaued in recent years (GenAge database).…”
Section: Challenges In Aging: Science Society and Economymentioning
confidence: 99%
“…The αKG/glutamine synthesis pathways may also be important in modulating the ability of diet restriction to increase lifespan 19 . More recently, it has been shown that the lifespan-extending effects of αKG are preserved in both flies 52 and mice 53 . In the future, it is imperative to investigate the impact of these metabolites and metabolic pathways on network structures and metabolic communications, and to better understand the mechanisms through which nutrient presentation influences lifespan.…”
Section: Discussionmentioning
confidence: 99%